Cell Therapy in Heart Failure with Preserved Ejection Fraction - Sabina Frljak; Gregor Poglajen; Bojan Vrtovec (Cardiac Failure Review)
Heart failure with preserved ejection fraction (HFpEF) is the most common cause of hospitalisation for heart failure. However, only limited effective treatments are available. Recent evidence suggests that HFpEF may result from a systemic proinflammatory state, microvascular endothelial inflammation and microvascular rarefaction. Formation of new microvasculature in ischaemic tissues is dependent on CD34+ cells, which incorporate into the newly developing vasculature and produce pro-angiogenic cytokines. In HFpEF patients, worsening of diastolic function appears to correlate with decreased numbers of CD34+ cells. Therefore, it is plausible that increasing the myocardial numbers of CD34+ cells could theoretically lead to improved microvascular function and improved diastolic parameters in HFpEF. In accordance with this hypothesis, recent pilot clinical data suggest that CD34+ cell therapy may indeed be associated with improved diastolic function and better functional capacity in HFpEF patients and could thus represent a promising novel therapeutic modality for this patient population.